Management of hydrocephalus associated with large vestibular schwannomas - Leslie Lemnos; Lucas Troude; Mohamed Boucekine; Stéphane Gargula; Anne Balossier; Jean Régis; Pierre-Hugues Roche (Brain and Spine)
Introduction: Some patients with vestibular schwannoma (VS) may present with hydrocephalus. Research question: In such cases, some authors suggest cerebrospinal fluid (CSF) shunting, while others prefer tumor removal from the outset. Material and methods: In our study, we retrospectively compared patients for whom we chose to treat the hydrocephalus with CSF shunting and those for whom VS surgery was performed first. Results: Among a group of n consecutive patients harboring a stage 3 and 4 VS and eligible for resection, 34 patients presented with hydrocephalus. Thirteen patients underwent CSF shunting (group 1). Twenty-one patients had their VS removed first (group 2). Among the latter group, 18 patients had resolution of hydrocephalus. There was a significant difference between group 1 and 2 in the presence of signs of intracranial hypertension (p = 0.00), preoperative tumor volume (p = 0.04).Previous radiosurgery and a strong adherence of the tumor capsule to the brain were statistically associated with requirement of CSF shunting (p = 0.01). Discussion and conclusion: The results of this study suggest that VS patients presenting with a well-tolerated hydrocephalus should be preferentially treated of their schwannoma with rare need for a shunt.